Resisting globalization? Turkey-EU relations and human and political rights in the context of cosmopolitan democratization - Rumford, C. (Sage Publications Ltd, 6 Bonhill Street, London Ec2A 4Pu, England, 2003)
Turkey's relationship with the European Union (EU) is dominated by issues of democratization and human rights and is best approached from a perspective which understands the nature of the cosmopolitan regimes which work to regulate the democratic practices of nation-states and animate citizens and minority groups striving to assert their rights. Cosmopolitan or transnational processes of democratization are frequently perceived by Turkey's Kemalist political elites as being contrary to the interests of domestic harmony and a threat to national integrity. It is argued that the apparent reluctance of the Kemalist elites to embrace greater pluralism and align with the EU's Copenhagen criteria is in fact an attempt to 'remake' themselves through political choices framed by global opportunities. In this sense, the mobilization of nationalist resistance to outside 'interference' is calculated to secure legitimacy in an increasingly uncertain political environment. In addition, Turkey is increasingly dependent upon the very global processes that are perceived as a threat to national sovereignty, and EU standards and norms offer the means by which Turkey can safeguard national integrity.
Keywords: cosmopolitanism; European Union; globalization; human rights; Kemalism; Turkey